Academic Cheating in Pesantren: How Self Efficacy, Religiosity, and Academic Integrity Predict Academic Cheating - Lestari, Wahidah Iskar; Latifa, Rena; Rahmah, Muthia (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThis research aims to determine the effect of self-efficacy, religiosity and academic integrity on academic cheating in Pesantren. The population of the research is consisted of students MA. Sample are 332 students and sampling technique is carried out using probability sampling, namely purposive sampling technique. The instrument used were ACS (Academic Cheating Scale), GSE (General Self Efficacy), DUREL (Duke Religion Index), and AIS (Academic Integrity Scale). Data analysis used in this study is multiple linear regression techniques and for the analysis of the construct validity used to measure instrument is Confimatory Factor Analysis CFA. The results of the study show that the effect of the variables of self-efficacy, the dimensions of organizational and dimensions intrinsic to academic cheating which was moderated by academic integrity are significant. Based on the results of the multiple linear regression with academic integrity as the moderator variable, shows that academic integrity has a significant effect or influence on academic cheating and also has a significant influence in moderating one independent variable, namely the organizational dimension to academic cheating. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh efikasi diri, religiusitas dan integritas akademik terhadap kecurangan akademik di Pesantren. Populasi dalam penelitian ini adalah mahasiswa MA. Sampel berjumlah 332 siswa dan teknik pengambilan sampel dilakukan dengan teknik probability sampling yaitu teknik purposive sampling. Instrumen yang digunakan adalah ACS (Academic Cheating Scale), GSE (General Self Efficacy), DUREL (Duke Religion Index), dan AIS (Academic Integrity Scale). Analisis data yang digunakan dalam penelitian ini adalah teknik regresi linier berganda dan untuk analisis validitas konstruk yang digunakan untuk mengukur instrumen adalah Confimatory Factor Analysis CFA. Hasil penelitian menunjukkan bahwa pengaruh variabel efikasi diri, dimensi organisasi dan dimensi intrinsik terhadap kecurangan akademik yang dimoderatori oleh integritas akademik adalah signifikan. Berdasarkan hasil regresi linier berganda dengan variabel moderator integritas akademik, menunjukkan bahwa integritas akademik berpengaruh atau berpengaruh signifikan terhadap kecurangan akademik dan juga memiliki pengaruh signifikan dalam memoderasi salah satu variabel independen yaitu dimensi organisasi terhadap kecurangan akademik.How to Cite Lestari, W. I., Latifa, R. Rahmah, M. (2022). Academic Cheating in Pesantren: How Self Efficacy, Religiosity, and Academic Integrity Predict Academic Cheating. TARBIYA: Journal of Education in Muslim Society, 9(2), 1-18. doi:10.15408/tjems.v9i1.24701.